2015
DOI: 10.12662/2317-3076jhbs.v3i3.186.p132-136.2015
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre hiperglicemia e morbimortalidade em pacientes críticos na Unidade de Terapia Intensiva de um hospital terciário de Fortaleza – CE <br> doi:10.12662/2317-3076jhbs.v3i3.186.p132-136.2015

Abstract: Introdução: A hiperglicemia é frequentemente associada ao aumento da morbimortalidade em Unidades de Terapia Intensiva. Objetivo: o objetivo deste estudo foi avaliar o impacto do controle glicêmico em pacientes criticamente enfermos. Métodos: Estudo transversal, em que foram revisados os prontuários de pacientes internados na UTI de um hospital público terciário. Foram analisados dois subgrupos de pacientes, um com 100 indivíduos que foram a óbito e outro com 100 indivíduos que receberam alta. Resultados: A mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The presence of comorbidities may reflect the greater susceptibility of the population with chronic diseases in developing sepsis. Among the most frequent comorbidities, are: heart failure, Diabetes Mellitus, Malignant neoplasia, chronic renal failure, chronic liver disease, high blood pressure and squeals of neurological diseases (6)(7)(8)(9)(10)(16)(17) , but this study showed more not diabetics patients.…”
Section: Discussionmentioning
confidence: 56%
“…The presence of comorbidities may reflect the greater susceptibility of the population with chronic diseases in developing sepsis. Among the most frequent comorbidities, are: heart failure, Diabetes Mellitus, Malignant neoplasia, chronic renal failure, chronic liver disease, high blood pressure and squeals of neurological diseases (6)(7)(8)(9)(10)(16)(17) , but this study showed more not diabetics patients.…”
Section: Discussionmentioning
confidence: 56%
“…Studies show that intensive glycemic control reduces multiple organ failure, systemic infections, the patient's length of stay in hospitals or ICUs, and even cases of mortality in critically ill patients, highlighting the need for strict control. [4] Although [5] recommend ideal blood glucose (target range) between 140 to 180 mg/dL, some authors including the specialist who contributes to this work say that this value may vary depending on the hospital in which it is applied. However, regardless of which is the ideal value the most important thing is to keep the monitoring.…”
Section: Introductionmentioning
confidence: 99%